Penerapan Batas Usia Pernikahan Di Dunia Islam: Review Literature - Hermanto, Agus; Ismail, Habib; Rahmat, Rahmat; Arsyad, Mufid (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2021)
Background.The application of Islamic family law has differences in Islamic countries. The differences stem from the interpretation and understanding of the relationship between Islam and the state (din wa siyasah), the ideological basis of the state, the Islamic style of the mainstream Muslim population, traditions and socio-cultural realities, and their respective historical backgrounds.Aim. This library research article review uses a philosophical and sociological approach in each country which sets the minimum age limit for marriage to examines the comparison of Islamic family law in the Islamic world.Results. The existence of Islamic family law in the world as positive law has different forms. There are three categories of countries based on the adopted family law; 1) Countries that apply traditional family law. Countries that fall into this category are Saudi Arabia. Yemen, Kuwait, Afghanistan, Mali, Mauritania, Nigeria, Sinegal, Somalia. 2) Countries that apply secular family law. Included in this category are Turkey, Albania, Tanzania, the Muslim minority of the Philippines. 3) Countries that implement the updated family law. countries in the category of carrying out substantive reforms and or regulatory reforms. The reform of Islamic family law was carried out for the first time in Turkey, followed by Lebanon and Egypt, Brunei, Malaysia and Indonesia.